Unveiling neonatal risk factors, clinical profile and early diagnostic markers of neonatal sepsis in a tertiary care hospital from South India: a cross-sectional study - Suman, Pradyotha; Kulkarni, Nagamani; Ukkali, Sadashiva B.; Thobbi, A. N. (International Journal of Contemporary Pediatrics, 2024)
Background: Neonatal sepsis remains a significant cause of morbidity and mortality in newborns, particularly in resource-limited settings. Understanding the clinical presentation, neonatal risk factors associated with neonatal sepsis and evaluating the correlation of markers of sepsis [C-reactive protein (CRP), white blood cell (WBC) counts, immature to total (IT) ratio and presence of toxic granules] for its early diagnosis are essential for improving the neonatal health outcomes. Methods: A cross-sectional study was conducted among 120 neonates admitted to the tertiary care hospital in Vijayapura, Karnataka, South India. Neonatal risk factors were assessed, and laboratory investigations were performed to diagnose neonatal sepsis. Statistical analysis was conducted to determine associations and significance. Results: The most prevalent symptom across all categories is tachypnea, observed in 98.3% of the total patients. Lethargy, refusal to suck, and fever are equally frequent, affecting 65.8% of the total patients. Neonatal risk factors such as prematurity and low birth weight were identified as important contributors to sepsis. WBC counts, elevated CRP levels (>0.6 mg/dl), IT ratio above 0.2, and presence of toxic granules were significantly associated with neonatal sepsis. Conclusions: Neonatal risk factors play a crucial role in the occurrence and outcome of neonatal sepsis. Laboratory investigations, particularly CRP levels, IT ratio, and toxic granule examination, demonstrate significant diagnostic value for the early diagnosis of neonatal sepsis.